Evaluation of nephrotoxicity and prognosis in patients treated with colistin due to hospital-acquired pneumonia - (:unkn) unknown (TURKISH ASSOC TUBERCULOSIS & THORAX, 2017)
Introduction: Colistimethate sodium (CMS) is frequently used in the treatment of nosocomial multidrug-resistant gram-negative infections. Nephrotoxicity is the most important side effect. The aim of this study is to evaluate the effect of colistin on nephrotoxicity and to assess prognosis in patients treated with CMS due to hospital-acquired pneumonia (HAP). Materials and Methods: Patients treated with CMS for HAP due to multidrug-resistant Pseudomonas aeruginosa or Acinetobacter baumannii were included in this cohort study. Results: We evaluated 281 patients treated with two different brands of CMS whose administration dose is different: imported (n=58, low dose/kg) and domestic (n=223, high dose/kg). Nephrotoxicity developed in 175 patients (62.3%). The median age (73 vs. 66 years, p=0.004) and mortality rates were higher (66.9% vs. 52.8%, p=0.022) in patients having nephrotoxicity. The patients receiving high dose/kg had higher nephrotoxicity rate (67.7% vs. 41.4%, p < 0.001). The clinical, bacteriological response and mortality rates of the whole group were 52.0%, 61.0%, 61.6%, respectively. The clinical and bacteriological response rates were similar in the different dose groups. Multivariate analysis showed that nephrotoxicity was associated with domestic brand depending on use of high dose (OR=3.97), advanced age (beta=0.29, p=0.008), male gender (OR=2.60), hypertension (OR=2.50), red blood cells transfusion (OR=2.54), absence of acute kidney injury (OR=10.19), risk stage of RIFLE (OR=11.9). Conclusion: Nephrotoxicity is associated with the use of high dose colistin, age, gender, hypertension, red blood cells replacement and RIFLE stage. The mortality rate is higher in patients developing nephrotoxicity.
Keywords: Nosocomial infection; pneumonia; multidrug resistant; colistimethate sodium; toxicity; RESISTANT ACINETOBACTER-BAUMANNII; VENTILATOR-ASSOCIATED PNEUMONIA; ACUTE-RENAL-FAILURE; INTENSIVE-CARE-UNIT; INTRAVENOUS COLISTIN; PSEUDOMONAS-AERUGINOSA; COLISTIMETHATE SODIUM; INFECTIONS; EFFICACY; THERAPY